Chronic care infrastructures and the home. Issue 7 (10th January 2013) - Langstrup, Henriette
Abstract: In this article I argue that attention to the spatial and material dimensions of chronic disease management and its place‐making effects is necessary if we are to understand the implications of the increased mobilisation – technologically or otherwise – of the home in chronic disease management. Analysing home treatment in asthma and haemophilia care, I argue that in relation to chronic disease management the home is not only always connected to the clinic but moreover, what the home is in part depends on the specificities of these attachments. Drawing primarily on the work of Susan Leigh Star and scholars of human geography I propose the concept of chronic care infrastructures designating the often inconspicuous socio‐material elements (such as medication, control visits, phone calls, doses and daily routines), which are embedded in everyday life (of both the clinic and the home) and participate in producing the effect of treatment but also the effect of home. These chronic care infrastructures demand the emplacement of various objects and activities in everyday life and thus relate to negotiations of 'keepings'– what to keep and care for and where to grant it room vis á vis other 'keepings'.